Narrowing the Curriculum? Contemporary Trends in Provision and Attainment in the Scottish Curriculum - Shapira, Marina; Priestley, Mark (Scottish educational review, 2018)
This paper forms the first part of research into the phenomenon of curriculum narrowing within Scotland's Curriculum for Excellence (CfE). It presents findings from a preliminary analysis of publicly available data -- Scottish Qualifications and school leavers' attainment data, aggregated by local authorities. Our findings show that the senior phase curriculum is becoming narrower. Fewer subjects are being taken in school year S4 for levels 4 and 5 National Qualifications. Yet, we found that the phenomenon of curriculum narrowing is more nuanced and complex than has been claimed. Attainment at SCQF levels 4-6 has risen since the introduction of the CfE and new national qualifications. The increase in the SCQF level 6 qualifications was particularly noticeable in more deprived local authorities. We acknowledge that the coarse grained nature of the available data makes our findings provisional; further phases of this research will address this through analysis of school level data.